From CFD to GIS: a methodology to implement urban microclimate georeferenced databases - Matteo Trane; Guglielmo Ricciardi; Mattia Scalas; Marta Ellena (Techne)
The objective of this paper is to present a methodology for the integration of a Computational Fluid Dynamics (CFD) microclimate simulation and a Geographic Information System (GIS). The first workflow involves the attribution of spatial coordinates to the point data extracted from the CFD, the implementation of an SQLite database, and the connection to the database to visualise and use information on environmental and comfort variables. The second workflow involves georeferencing the CFD raster output, attributing an ID to the point data, creating a point grid in a GIS environment, and merging these with the point data on the microclimate. For demonstration purposes, the methodology is tested on a real case study using ENVI-met and ArcGIS Pro.